Pengaruh ModeI Problem Based Learning Terhadap Higher Order Thinking SkiIIs Siswa - Laras Sinta; Khairul Saleh; Rega Armela (PT. Berkah Smart Academica, 2025)
Problem Based Learning (PBL) is an innovative learning modeI that provides active Iearning condotions to student through presenting ProbIems to be solved. PBL is a effective modeI for improving students’ higher thinking SkiIIs (HOTS), Higher Order Thinking SkiIIs (HOTS) is a process of higher order thinking SkiIIs that students need to master in the process of Iearning to solve ProbIems. This study aims to determine the magnitude of the influence of the PBL modeI on HOTS. This research is an ex post facto quantitative study, and the population of this study was 94 students of class XI. Data collection was carried out by distributing questionnaires, observation, documentation and interview. Dara were analyzed using the Correlations Product Moment formuIa and t-test using IBM SPSS 25. The result related to the influence of ProbIem based Iearning modeIs on higher order thinking SkiIIs by testing the product moment correlation test obtained an rcount value of 0,733 > rtabIe 0,20 indicating a strong relationship level. And the results of test-t stated that there was a significant effect because 0,000<0,05 and the t count 10,332> t tabIe 1, 986 which means Ho was rejected and Ha was accepted. The coefficient of determination test shows that the significant influence of variable X on variable Y is 73,3%, so it can be concluded that the better the application of the PBL modeI. used, it will increase students' higher order thinking SkiIIs/HOTS.